357 GLS-010 (Zimberelimab), a novel fully human anti-PD-1 mAb in chinese patients with recurrent/metastatic cervical cancer: results from a multicenter, open-label, single-arm phase II trial. (13th November 2020) - Wu, X; Xia, L; Zhou, Q; Zhu, J; Wang, K; Chen, J; Huang, Y; Kurb, G; Chang, B; Zhao, W; Wang, X; Yang, Y; et al.
Abstract : Introduction: GLS-010 (Zimberelimab) is a novel fully human anti-PD-1 monoclonal antibody developed on the OMT transgenic rat platform, exhibiting good tolerance and pre-liminary efficacy in previous phase I study. Methods: In this open-label phase II clinical trial (NCT03972722 ), PD-L1 positive (combined positive score (CPS) ≥1) patients with recurrent or metastatic cervical cancer who had received one or more lines of chemotherapy were enrolled. All patients received GLS-010 240 mg every 2 weeks. Objective response was evaluated by RECIST v1.1. AEs were graded by NCI-CTCAE, version 4.03. Results: A total of 45 patients with recurrent or metastatic cervical cancer were enrolled. As of April 2, 2020, of 41 evaluable patients, 11 achieved an objective response by investigator assessment with an ORR of 26.83% and a DCR of 53.66%. After a median follow-up time of 5.2 months (range:1.6–9.7), 18 patients still remained on treatment and 27 of them discontinued treatment due to progressive disease or adverse events. The Median DOR had not been reached yet. 36 of 45 (80.00%) patients experienced one or more treatment-related adverse events(TRAE), most of which were Grade 1 or 2.≥Grade 3 TRAEs occurred in 17 (37.78%) patients, and the most common one was Anaemia. Only 1 patient discontinued treatment due to adverse event. Conclusion: GLS-010 (Zimberelimab) showed encouraging therapeutic activity and manageable safety profile in Chinese recurrent or metastatic cervical cancer patients. This study is still ongoing, and we are looking forward to further results.